Fragmentation by design: Universal health coverage policies as governmentality in Senegal - Mladovsky, Philipa (Social science & medicine (1982), 2020)
There is increasing international consensus that countries need to reduce health system fragmentation in order to achieve universal health coverage (UHC). Yet there is little agreement on what drives fragmentation, in particular the extent to which fragmentation has a political purpose. This study analyses a highly fragmented health financing system through a UHC policy that aims to remove user fees for people aged 60 and over in Senegal. 53 semi-structured interviews (SSIs) and focus group discussions with the target population were conducted in four regions in Senegal over a period of six months during 2012. A further 46 SSIs were conducted with key informants at the national level and in each of the four regions. By analysing explanations of the successes and failures of policies, an understanding of power relations in state institutions, communities and individuals is gained. The concept of governmentality is used to interpret the results. The interviewees’ main concern was to implement or resist various techniques of control over the conduct of bureaucrats, health workers, patients and the wider population. These techniques included numeracy and calculation, referral letters, ID cards, data collection, new prudentialism, active citizenship and ethical self-formation through affinities of the community. The techniques sought to make two types of subjects; citizens subjects of rights and obligations; and autonomous subjects of choice and self-identity. A key implication is that in Senegal, and perhaps elsewhere, fragmentation of the health system plays a key role in the formation and control of subjects, in the name of “freedom”. As such, fragmentation may be an inherent feature of UHC. Interventions that aim to reduce fragmentation based on evidence of its inefficiency, inequity and ineffectiveness in reducing poverty and ill health may be missing this point. •UHC's role in making citizen subjects and autonomous subjects is underestimated.•Making subjects is a key political driver of UHC fragmentation.•Interventions that aim to reduce fragmentation overlook this rationality of UHC.•Fragmentation may be an inherent feature of UHC.